2018
DOI: 10.3390/en11102665
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Interplay between CAD and FreeFem++ as an Energy Decision-Making Tool for Architectural Design

Abstract: The energy modelling software tools commonly used for architectural purposes do not allow a straightforward real-time implementation within the architectural design programs. In addition, the surrounding exterior spaces of the building, including the inner courtyards, hardly present a specific treatment distinguishing these spaces from the general external temperature in the thermal simulations. This is a clear disadvantage when it comes to streamlining the design process in relation to the whole-building ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Although there are many simulation tools to predict the energy performance of buildings, the complex thermodynamic effects that happen in courtyards require simulation tools with high computational resources and thousands of simulation hours to calculate and simulate a representative period, based on CFD (Computational Fluid Dynamics) and finite elements (Blocken et al 2011). In the analysis performed by Rojas et al (Rojas-Fernández et al 2018), the main available simulation tools are analysed concerning their capacity to simulate transitional spaces from the point of view of a professional of the building sector. They found that there is no available software that meets all requirements for this reliable microclimate simulation.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are many simulation tools to predict the energy performance of buildings, the complex thermodynamic effects that happen in courtyards require simulation tools with high computational resources and thousands of simulation hours to calculate and simulate a representative period, based on CFD (Computational Fluid Dynamics) and finite elements (Blocken et al 2011). In the analysis performed by Rojas et al (Rojas-Fernández et al 2018), the main available simulation tools are analysed concerning their capacity to simulate transitional spaces from the point of view of a professional of the building sector. They found that there is no available software that meets all requirements for this reliable microclimate simulation.…”
Section: Introductionmentioning
confidence: 99%
“…The courtyard microclimate can be explained in terms of the thermodynamic effects that occur within it, i.e., convection, radiation, stratification, and flow patterns. Among the different parameters affecting these microclimatic conditions, most of the studies emphasize the importance of courtyard geometry [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], in many cases considered the Aspect Ratio (AR), which is the ratio between the height and the width of the courtyard.…”
Section: Introductionmentioning
confidence: 99%
“…Courtyard location, implying climatic conditions and specifically outdoor temperature ranges, is another key factor that is becoming commonplace in a large number of publications [14][15][16][17][18][19][20][21][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the tools that consider the optimisation of energy systems with detailed building models [13,20], this article focuses on the tools that make a compromise between the accurate calculations of the physical properties of one building, and the optimisation of these properties for multiple buildings and the components of their energy systems. Such tools that can optimise the energy system for a settlement or urban quarter are already available (e.g., RETScreen [21] and the tools developed by the passive house institute).…”
Section: Introductionmentioning
confidence: 99%